Основные аспекты методологии проектирования воздушных линий при "интеллектуализации" электрических сетей - Черкашина, Вероника Викторовна (НТУ "ХПІ", 2016)
В статье показаны основные аспекты современной методологии проектирования воздушных линий, которые учитывают при "интеллектуализации" электрических сетей оптимизацию параметрического ряда сечений проводов и расширение технологического базиса их функциональных возможностей, что позволит выполнить переход линий от "пассивных" к активно-аддаптивным объектам электрических сетей.

During "intellekt" of electric networks air-tracks must be artiv - by addaptiv objects, that dictates the necessity of new approach for methodology of planning airtracks. In the article the basic aspects of methodology of planning of air-tracks are presented during "intellekt" of electric networks. It is shown that forming of modern methodology of planning of air-tracks must consist of two stages: on the first stage optimization of self-reactance row of sections of wires is expedient taking into account the prospect of functioning of air-tracks, that similarly will allow partly to decide the questions of decline of heterogeneity of network; on the second stage it is expedient to envisage the equipment of these lines the additional elements of estimation and control, that extend the technological base of functional possibilities of lines due to additional information about parameters in the mode of "on-line", what the transition of lines will allow to execute from "passive" to the artiv-addaptiv objects electric networks.
An account parameters of environment is in the tasks of planning airtracks
Keywords: электросетевой комплекс; критериальный метод; активно-адаптивный объект; "интелектуальная" сеть; kriterial method; actively-adaptive object; electric network; "intellekt" network